Polyphenols as fungal phytotoxins, seed germination stimulants and phytoalexins - Cimmino, Alessio; Andolfi, Anna; Abouzeid, Mohamed; Evidente, Antonio (PHYTOCHEMISTRY REVIEWS, 2013)
This review deals with the sources and chemical and biological characterization of phytotoxic polyphenols produced essentially by pathogenic fungi of forest and crop plants and of weeds. Their potential use as natural herbicides and fungicides is discussed. The use of some polyphenols which could be applied as an alternative method to control parasitic weeds, the so called ``suicidal germination{''}, will be covered. The sources and the isolation and identification of polyphenols produced by some crop plants in consequence of the attack of pathogenic fungi as plant defence compounds (phytoalexins), are also described.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Phytoalexins; Phytotoxins; polyphenols; Seed germination stimulants

Afritoxinones A and B, dihydrofuropyran-2-ones produced by Diplodia africana the causal agent of branch dieback on Juniperus phoenicea - Evidente, Antonio; Masi, Marco; Linaldeddu, Benedetto T.; Franceschini, Antonio; Scanu, Bruno; Cimmino, Alessio; Andolfi, Anna; Motta, Andrea; Maddau, Lucia (PHYTOCHEMISTRY, 2012)
Two phytotoxic dihydrofuropyran-2-ones, named afritoxinones A and B. were isolated from liquid culture of Diplodia africana. a fungal pathogen responsible for branch dieback of Phoenicean juniper in Italy. Additionally, six others known metabolites were isolated and characterized: oxysporone, sphaeropsidin A, epi-sphaeropsidone, R-(-)-mellein, (3R,4R)-4-hydroxymellein and (3R,4S)-4-hydroxymellein. The structures of afritoxinones A and B were established by spectroscopic and optical methods and determined to be as (3aS{*},6R{*}-,7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-o ne and (3aR{*},6R{*},7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-on e, respectively. The phytotoxic activity of afritoxinones A and B and oxysporone was evaluated on host (Phoenicean juniper) and non-host plant (holm oak, cork oak and tomato) by cutting and leaf puncture assay. Oxysporone proved to be the most phytotoxic compound. This study represents the first report of secondary metabolites produced by D. africana. In addition, the taxonomic implications of secondary metabolites in Botryosphaeriaceae family studies are discussed. (C) 2012 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Afritoxinones A and B; Botryosphaeriaceae; Diplodia africana; Juniperus phoenicea; Phytotoxins

Cyclobotryoxide, a phytotoxic metabolite produced by the plurivorous pathogen Neofusicoccum australe. - Andolfi, Anna; Maddau, Lucia; Cimmino, Alessio; Linaldeddu, Benedetto T.; Franceschini, Antonio; Serra, Salvatorica; Basso, Sara; Melck, Dominique; Evidente, Antonio (Journal of natural products, 2012)
Two isolates of Neofusicoccum australe belonging to ITS haplotypes H4 and H1 and associated with grapevine cordon dieback and branch dieback of Phoenicean juniper, respectively, have been shown to produce in vitro structurally different secondary metabolites. From the strain BOT48 of N. australe (haplotype H4) a new cyclohexenone oxide, namely, cyclobotryoxide, was isolated together with 3-methylcatechol and tyrosol. Cyclobotryoxide was characterized as (1S,5R,6S)-5-hydroxy-3-methoxy-4-methyl-7-oxabicyclo[4.1.0]hept-3-en-2-one by spectroscopic, optical, and chemical methods. The strain BL24 (haplotype H1) produced tyrosol along with botryosphaerone D and (3S,4S)-3,4,8-trihydroxy-6-methoxy-3,4-dihydro-1(2H)-naphthalenone. The metabolites obtained from both strains were tested at four concentrations on leaves of grapevine cv. Cannonau, holm oak, and cork oak by the leaf puncture assay. Cyclobotryoxide proved to be the most phytotoxic compound. Tyrosol and cyclobotryoxide were also tested on detached grapevine leaves at concentrations of 0.25 and 0.5 mg/mL. Only cyclobotryoxide was found to be active in this bioassay.
The following values have no corresponding Zotero field: accession-num: 23046443
Keywords: Ascomycota; Ascomycota: chemistry; Bicyclo Compounds, Heterocyclic; Bicyclo Compounds, Heterocyclic: chemistry; Bicyclo Compounds, Heterocyclic: isolation & purif; Bicyclo Compounds, Heterocyclic: pharmacology; Catechols; Cyclohexanones; Cyclohexanones: chemistry; Cyclohexanones: isolation & purification; Cyclohexanones: pharmacology; Juniperus; Juniperus: microbiology; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Mycotoxins: isolation & purification; Mycotoxins: pharmacology; Nuclear Magnetic Resonance, Biomolecular; Quercus; Quercus: drug effects; Stereoisomerism; Vitis; Vitis: drug effects

Relationships between the stereochemistry and biological activity of fungal phytotoxins - Evidente, Antonio; Andolfi, Anna; Cimmino, Alessio (Chirality, 2011)
Toxins produced by phytopathogenic fungi assume great importance because of their involvement in several plant diseases. Although such pathogens are known to have seriously damaged crops, forest, and environmental resources, they represent a very important tool to develop new environmentally friendly herbicides and fungicides. This review deals with the relationships between the biological activity of some phytotoxins produced by pathogenic fungi for major forest plants and for damaging weeds and their stereochemistry. In particular, the methods used to determine their relative and/or absolute configuration will be illustrated. These include the application of Mosher's and Murata's methods, X-ray diffractometric analysis, circular dichroism, and the use of computational methods to determine the theoretical optical rotatory power as well as the CD spectrum. The importance of determining the absolute configuration to achieve the total synthesis of some phytotoxins, interesting for their potential practical application, is also discussed. Chirality, 2011. © 2011 Wiley-Liss, Inc.
The following values have no corresponding Zotero field: publisher: Wiley Subscription Services, Inc., A Wiley Company
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships

Sphaeropsidones, Phytotoxic Dimedone Methyl Ethers Produced by Diplodia cupressi: A Structure−Activity Relationship Study - Evidente, Antonio; Maddau, Lucia; Scanu, Bruno; Andolfi, Anna; Masi, Marco; Motta, Andrea; Tuzi, Angela (Journal of Natural Products, 2011)
Sphaeropsidone and episphaeropsidone are two phytotoxic dimedone methyl ethers produced by Diplodia cupressi, the causal agent of a canker disease of cypress in the Mediterranean area. In this study, eight derivatives obtained by chemical modifications and two natural analogues were assayed for phytotoxic and antifungal activities, and a structure?activity relationship was examined. Each compound was tested on nonhost plants and on five fungal pathogenic species belonging to the genus Phytophthora. The results provide insights into structure?activity relationships within these compounds. It was found that the hydroxy group at C-5, the absolute C-5 configuration, the epoxy group, and the C-2 carbonyl group appear to be structural features important in conferring biological activity. The conversion of sphaeropsidone into the corresponding 1,4-dione derivative led to a compound showing greater antifungal activity than its precursor. This finding could be useful in devising new natural fungicides for practical application in agriculture.
doi: 10.1021/np100837rdoi: 10.1021/np100837rThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: antifungal activity (voyant); Diplodia cupressi; Phytotoxicity; Sphaeropsidones

Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.
Keywords: canker disease; Cork oak; Diplodia corticola; phytotoxic metabolites; Quercus suber L.

Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.

Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393l

Diplobifuranylones A and B, 5‘-Monosubstituted Tetrahydro-2H-bifuranyl-5-ones Produced by Diplodia corticola, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela; Maddau, Lucia; Franceschini, Antonio; Marras, Francesco; Motta, Andrea (Journal of Natural Products, 2006)
Two new 5?-monosubstituted tetrahydro-2H-bifuranyl-5-ones, named diplobifuranylones A and B (1 and 2), were isolated from the culture filtrates of Diplodia corticola, the causal agent of a canker of cork oak (Quercus suber). The same fungus also produced eight known metabolites, namely, the diplopyrone, (3S,4R)-trans- and (3R,4R)-cis-4-hydroxymellein, sapinofuranone B and its (S,S)-enantiomer, and sphaeropsidins A?C. Diplobifuranylones A and B (1 and 2) were characterized, using spectroscopic and chemical methods, as two diastereomeric 5?-(1-hydroxyethyl)-3,4,2?,5?-tetrahydro-2H-[2,2?]bifuranyl-5-ones. While the relative stereochemistry of the two metabolites (1 and 2) was deduced by NOESY and ROESY experiments, the absolute stereochemistry of the chiral carbon of the hydroxyethyl side chain at C-5?, determined by application of Mosher's method, proved to be S and R in 1 and 2, respectively. Assayed on a nonhost plant, diplobifuranylones A and B did not show phytotoxic activity. In an Artemia salina larvae lethality bioassay neither 1 nor 2 was toxic at the highest concentration tested (300 ?g/mL).
doi: 10.1021/np050393ldoi: 10.1021/np050393lThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Chemical characterization; Diplobifuranylones; Diplodia corticola; metabolites; Phytotoxicity (voyant)